1998
DOI: 10.1002/(sici)1099-0690(199811)1998:11<2519::aid-ejoc2519>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure of Biologically Active Gangliosides from the Sea CucumberHolothuria pervicax

Abstract: Three ganglioside molecular species, HPG‐8, HPG‐3, and HPG‐1, have been obtained from the polar fraction of the chloroform/methanol extract of the sea cucumber Holothuriapervicax. The structures of these gangliosides have been determined on the basis of chemical and spectroscopic evidence. They represent new ganglioside molecular species. HPG‐8 is a sulfated monosialo‐ganglioside, while HPG‐3 and HPG‐1 are disialo‐gangliosides possessing 2→4‐linked tandem‐type disialosyl moieties. These three gangliosides qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In the study of the GSLs of the sea cucumber Holothuria pervicax (Torafunamako in Japanese), we reported the isolation and structure of four new ganglioside molecular species. 5,7) Continuing the preceding studies, the isolation and characterization of cerebrosides from H. pervicax was conducted. In this paper, we report the isolation and characterization of glucocerebrosides from the whole bodies of H. pervicax.…”
mentioning
confidence: 99%
“…5,7) Continuing the preceding studies, the isolation and characterization of cerebrosides from H. pervicax was conducted. In this paper, we report the isolation and characterization of glucocerebrosides from the whole bodies of H. pervicax.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Continuing the previous studies, our search for the biologically active ganglioside from the sea cucumber Stichopus chloronotus (shikakunamako in Japanese) has led to the isolation of three ganglioside molecular species designated SCG-1, SCG-2, and SCG-3. In this paper, we report on the isolation and characterization of these three gangliosides from the body walls of S. chloronotus.…”
mentioning
confidence: 90%
“…5,13) In addition, the absolute configuration of the Glc unit was verified to be the D-form using the Hara et al method. 14) Consequently, if NeuGc, which is commonly found in natural sources, is assumed to be of the D-series, then SCG-1 is the (N-glycolyl-a -D-neuraminosyl)-(2→6)-b -D-glucopyranoside of a ceramide composed of heterogeneous (2S,3R,4E)-sphingosine and (2R)-2-hydroxy fatty acid units.…”
mentioning
confidence: 99%